PRINSIP KERJASAMA MAKSIM DAN IMPLIKATUR PADA SERI FILEM â€œEIFFEL Iâ€™M IN LOVEâ€ - Budiarta I Wayan; Loktika Nengah Nita; Renaya Nengah (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2020)
The purpose of this research is to describe the violations of the maxims and implicatures on the principle of cooperation that was found in the film Eiffel I'm in Love series. The data were collected by the documentation method. The theory mentioned by Grice (1975) and Thomas (1995) was used in analyzing the data. The research findings revealed that there were five types of cooperation principle violations are found in the movie. These are caused by the failure of the participant in understanding the maxims, namely violation, flouting, infringing, opting out, and suspending. The types of maxim violated are the quantity, quality, relativity, implementation, or methods. Implications from maxim violations mean: avoidance, misunderstandings, reject invitations, ignore the other person, and politeness.